2018
DOI: 10.1155/2018/5171582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Combined Effects of Heat and Lighting on the Level of Attention and Reaction Time: Climate Chamber Experiments in Iran

Abstract: Heat exposure and unsuitable lighting are two physical hazardous agents in many workplaces for which there are some evidences regarding their mental effects. The purpose of this study was to assess the combined effect of heat exposure and different lighting levels on the attention rate and reaction time in a climatic chamber. This study was conducted on 33 healthy students (17 M/16 F) with a mean (±SD) age of 22.1 ± 2.3 years. The attention and reaction time test were done by continuous performance test and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It seems, therefore, that a high level of physical activity may blur gender differences in a simple reaction to a visual stimulus [30]. Various external stimuli, e.g., heat, light intensity [31], noise [32] and other external and internal factors (e.g., mental fatigue [33]) can significantly affect SRT. In laboratory conditions, the boys obtained the shortest simple reaction times, and the differences between the dynamic and static conditions during the study in the natural external environment were not statistically confirmed (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…It seems, therefore, that a high level of physical activity may blur gender differences in a simple reaction to a visual stimulus [30]. Various external stimuli, e.g., heat, light intensity [31], noise [32] and other external and internal factors (e.g., mental fatigue [33]) can significantly affect SRT. In laboratory conditions, the boys obtained the shortest simple reaction times, and the differences between the dynamic and static conditions during the study in the natural external environment were not statistically confirmed (Figure 7).…”
Section: Discussionmentioning
confidence: 99%